Analisis Pengaruh Desentralisasi Fiskal Terhadap Pertumbuhan Ekonomi Daerah Di 12 Kabupaten/Kota Provinsi Riau Tahun 2012-2020 - Abdul Azis; Dahlan Tampubolon; Selly Prima Desweni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
This study aims to analyze the effect of Fiscal Decentralization on regional economic growth in 12 districts/cities of Riau Province from 2012-2020. Some of the variables studied for their influence on regional economic growth are General Allocation Funds (DAU), Revenue Sharing Funds (DBH), Special Allocation Funds (DAK) and Regional Original Income (PAD) from 12 districts/cities in Riau Province. While the variable that describes Economic Growth is Gross Regional Domestic Income (GRDP) in 12 districts/cities in Riau Province. In this study, the analysis was carried out using the Chow Test and Hausman Test methods. The model chosen is the Fixed Effect Model (FEM). This research uses panel data at the Regency/City level in Riau Province from 2012-2020. The results of the analysis conclude that DBH, DAK and PAD have a positive and significant impact on regional economic growth in 12 districts/cities in Riau Province. While the DAU variable has a negative and insignificant effect on regional economic growth in 12 districts/cities in Riau Province.